COVID-19 disruption strategy for redesigning global supply chain network across TPP countries - Takaki Nagao; Hiromasa Ijuin; Tetsuo Yamada; Keisuke Nagasawa; Lei Zhou (Logistics, 2022)
Background: COVID-19 has disrupted and adversely affected supply chains worldwide. A global supply chain network that considers disruptions is needed. This study strategically analyzes the economic and structural effects of disruption on a global supply chain network with customs duty and the trans-pacific partnership (TPP) agreement. Methods: We present a cost minimization model which helps in understanding the difficulty of supplying materials or products to factories or customers if the supplier's cities are facing disruption. This enables us to model and evaluate simultaneous considerations of supplier disruption, customs duty, and TPP in redesigning a global supply chain network. This network is modeled and formulated using integer programming, disruption scenarios, and a sensitivity analysis for customs duty. Results: Regarding the impact of disruptions on suppliers, two patterns emerge in the reconfigured network: direct changes due to supplier disruptions and indirect changes due to factory relocation. The sensitivity analysis for customs duty shows that the TPP has a positive impact on cost maintained, even in the presence of disruptions. Conclusions: Suppliers should be switched depending on the scale of disruption; when many distant suppliers need to be switched, the factory should be relocated to the country where these suppliers are located.
Keywords: 650; bill of material (BOM); business continuity plan (BCP); free trade agreement (FTA); integer programming (IP); pandemic plan; resilience; resilient supply chain